Stress and Academic Burnout among Nursing Students: A Regression Analysis - Villan, Christian; Cunanan, Gloria (Journal of Interdisciplinary Perspectives, 2025)
Attending nursing school is challenging. Students enrolled in a nursing program often complain of being academically burned out. As an educator, seeing, interacting with, and teaching learners suffering from burnout is tough. Nurse educators must be aware of this issue and act toward its resolution. Stress is a known predictor of burnout (Hwang & Kim, 2022). However, a gap exists in that current studies were focused on assessing these factors from countries outside the Philippines and only in the context of public educational institutions. Therefore, this article aims to close the gap by elucidating how stress predicts academic burnout in nursing students at both public and private colleges. The inquiry was participated in by 719 nursing students from 4 private and state universities in the Philippines, utilizing modified standardized questionnaires and a 5-point Likert scale. Pearson Product Moment Correlation and linear regression were also employed as statistical tools. The results revealed that student nurses were experiencing high levels of stress (M=3.89, SD=.977) and academic burnout (M=3.65, SD=1.10), implying that nursing learners studying in universities suffered from burnout and academic stress. Moreover, personal inadequacy, fear of failure, and inadequate study facilities were predictors of academic burnout, signifying these elements as crucial in shaping the students’ psychological well-being. Recognizing the factors causing academic burnout among student nurses is a significant step toward enhancing the quality of education. Furthermore, policymakers, administrators, and educators can develop and implement regulations that advocate for a healthier school life by understanding students' challenges.